2017
DOI: 10.1080/20464177.2017.1286841
|View full text |Cite
|
Sign up to set email alerts
|

A modified exponential score function for troubleshooting an improved locally made Offshore Patrol Boat engine

Abstract: In this paper, we present an Intuitionistic Fuzzy Technique for Order Preference by Similarity to the Ideal Solution model which is based on a modified exponential score function for detecting early failure in a locally made Offshore Patrol Boat engine, with special regard to component interaction failure, using groups of experts' opinions to detect the root cause and the engine systems most affected by the failures in the Boat engine. The study is aimed at providing an alternative method for the traditional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…IF-TOPSIS is one of the most widely used MCDM techniques [27]. It measures distances in the Euclidean norm, which implicitly assume all contemplated attributes are independent.…”
Section: Intuitionistic Fuzzy Technique For Order Of Preference By Simentioning
confidence: 99%
“…IF-TOPSIS is one of the most widely used MCDM techniques [27]. It measures distances in the Euclidean norm, which implicitly assume all contemplated attributes are independent.…”
Section: Intuitionistic Fuzzy Technique For Order Of Preference By Simentioning
confidence: 99%
“…Five probable failures (criteria) in the engine systems [13], [18] have been identified and they are consolidated with the experience and opinions of the experts, these criteria and their subs-criteria include;…”
Section: Application Of the Fse Methods And Intuitionistic Fuzzy Topsimentioning
confidence: 99%
“…Unlike the traditional FS, the IFS is characterized by a membership and a non-membership function, hence making it more capable of handling vagueness and uncertain information in practice. Extensive literature review has shown, significant increase in the application of the IFS over the past few years mostly for solving multi-criteria decision making (MCDM) problems (Aikhuele & Turan, 2017;Bai, 2013;Chen & Chiou, 2015;Jahromi, 2012;Li, 2005;Linet al , 2007;Liu & Ren, 2014;Xu, 2014). One of such applications includes the intuitionistic fuzzy technique for order preference by similarity to ideal solution (IF-TOPSIS).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhaiet al (2009), the methods and approaches can be classified into two categories, namely the numerical methods and the non-numerical methods. The non-numerical approach, basically involves the traditional design evaluation approach which includes methods like; concept screening (Ulrich, & Eppinger, 2000) and concept selection and evaluation (Pugh, 1996), while the numerical methods comprises of methods like decision matrixes (King & Sivaloganathan, 1999), quality function deployment (Mariniet al , 2016), fuzzy set (FS) concepts (Aikhuele & Turan, 2017;Akay et al, 2011;Jenab et al, 2013;Liu 2011), grey relation analysis (Zhai et al, 2009). …”
Section: Introductionmentioning
confidence: 99%